RF1 Gene Mutation in Familial Hemophagocytic Lymphohistiocytosis 2: A Family Report and Literature Review - Shi Y; Qiao Z; Bi X; Zhang C; Fu J; Jia Y; Yang G (Dove Medical Press, 2021)
Yuan Shi,* Zhidong Qiao,* Xiaoduo Bi, Chenxin Zhang, Junxian Fu, Yuexin Jia, Guanglu Yang Department of Pediatric, The Affiliated Hospital of Inner Mongolia Medical University, Hohhot, 010000, People's Republic of China*These authors contributed equally to this workCorrespondence: Guanglu YangDepartment of Pediatric, The Affiliated Hospital of Inner Mongolia Medical University, No. 1 Tongdao North Road, Hohhot, Inner Mongolia Autonomous Region, Hohhot, 010000, People's Republic of ChinaTel +86 13451311622Email yamgguamglu471@163.comObjective: Gene mutation analysis was performed on a family with familial hemophagocytic lymphohistiocytosis (FHL) so as to provide an accurate etiological diagnosis, leading to genetic counseling for the family members.Methods: The clinical data of two probands (siblings) with FHL in one family were analyzed, and eight genes related to the onset of the primary hemophagocytic lymphohistiocytosis (pHLH) (PRF1, UNC13D, STX11, STXBP2, SH2D1A, BIRC4/XIAP, Rab27a, LYST) were detected and analyzed in the probands and their parents with whole exome sequencing.Results: Proband 1 was a two-year-old male with the clinical manifestations of fever, hepatosplenomegaly, and a decreased peripheral blood cell count, sCD25: 12504pg/mL. The results of genetic testing showed that there was a c.1349C>T heterozygous missense mutation and a c.853_855del heterozygous mutation in the PRF1 in proband 1. Proband 2 was an eight-year-old female with the clinical manifestations of convulsions and disturbance of consciousness with fever. The genetic test results were the same as those of proband 1. There was a single heterozygous mutation in the parents of the probands, and both probands had compound heterozygous mutations.Conclusion: According to the clinical manifestations, laboratory tests, and results of the family molecular genetic testing, the probands could be clinically diagnosed as FHL2. The results of gene sequencing revealed that this was an autosomal recessive family with familial hemophagocytic syndrome. A rare pathogenic mutation (c.853_855del) in the PRF1 was discovered in the two patients with HLH.Keywords: FHL, PRF1, novel mutation